PENGEMBANGAN CD INTERAKTIF MACROMEDIA FLASH BERBASIS NILAI KARAKTER SUBTEMA 1 AKU DAN CITA-CITAKU KELAS IV - Setiyani, Ulfah Fitria; Wijayanti, Arfilia; Artharina, Filia Pria (Jurnal Sinektik, 2019)
The background that drives this research was the lack of 2013 curriculum learning media in the form of technology-based applications. The purpose of the study determined the feasibility of media-based interactive CD macromedia flash media. The type of research used is Research and Development (RnD) with the ADDIE model. Data analysis techniques used descriptive qualitative and quantitative descriptive. The results of the feasibility based on data analysis by expert experts obtain an average percentage of 94.17% for media feasibility, 95.00% for material feasibility and 91.67% for the feasibility of character values. The acquisition of teacher responses to media acceptance obtained a percentage in SD N Sawah Besar 02 of 86.67%, Elementary School of Muhajirin at 100.00% and SD N Siwalan obtained a percentage of 96.67%. The results of the questionnaire responses of the students obtained 96.36% in SD N Sawah Besar 02 and 93.64% in the Primary Schools of the Muhajirin. Media based on interactive CD macromedia flash based on the value of the character of sub-theme I and my ideals have met the criteria very well and are worthy of being used in the learning process.